Pengaruh Harga dan Brand image terhadap Keputusan Pembelian di Shopee dengan Labelisasi Kosmetik Halal sebagai Mediasi pada Mahasiswi UNHASY Tebuireng - Mumtazah, Azzayatul Rahma; Yuni K, Khusnul Ciptanila; Haryanti, Peni; Hidayati, Athi’ (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
This study aims to analyze the influence of price and brand image on purchasing decisions on Shopee, with halal cosmetics labeling as a mediating variable, among female students at UNHASY Tebuireng. This study is motivated by the growing halal cosmetics industry in Indonesia and the widespread use of the Shopee platform as a means of purchasing cosmetics online. When making purchasing decisions, Muslim women not only consider price and brand image but also pay attention to the halal status of products, which is verified through halal labeling. This study employs a quantitative approach using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. Data was collected through a questionnaire distributed to female students at UNHASY Tebuireng who had previously purchased cosmetics on Shopee. The results of the study indicate that price has a positive and significant effect on purchasing decisions, brand image has a positive and significant effect on purchasing decisions, and halal cosmetics labeling has a positive and significant effect on purchasing decisions. Furthermore, halal cosmetics labeling was found to mediate the effect of brand image on purchasing decisions but did not mediate the effect of price on purchasing decisions. These findings suggest that decisions to purchase cosmetics are influenced not only by economic factors and brand image but also by consumers’ awareness of the halal status of the products they use.